2019
DOI: 10.1038/s41598-019-43860-w
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in working memory capacity and cue-guided behavior in humans

Abstract: Information gathered via Pavlovian and Instrumental learning can be integrated to guide behavior, in a phenomenon experimentally known as Pavlovian-to-Instrumental Transfer (PIT). In particular, in appetitive PIT, a reward-associated cue is able to enhance the instrumental response previously associated with the same (outcome-specific PIT), or a similar (general PIT), reward. The PIT effect is increasingly investigated for its numerous implications in clinical contexts as well as daily life situations. Neverth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 62 publications
10
44
0
Order By: Relevance
“…absence of transfer. A higher transfer index (indicating a higher number of congruent than incongruent responses) was reported during seen trials (t (14) = 4.49; p = 0.001; 95% CI [0.33, 0.94]; BF 10 = 69.67) but not during unseen trials (t (14) = − 0.09; p = 0.9; 95% CI [− 0.72, 0.66]; BF 10 = 0.32) was reported (Fig. 4).…”
Section: Experiments 1 Instrumental Training Number Of Responses Tomentioning
confidence: 94%
See 2 more Smart Citations
“…absence of transfer. A higher transfer index (indicating a higher number of congruent than incongruent responses) was reported during seen trials (t (14) = 4.49; p = 0.001; 95% CI [0.33, 0.94]; BF 10 = 69.67) but not during unseen trials (t (14) = − 0.09; p = 0.9; 95% CI [− 0.72, 0.66]; BF 10 = 0.32) was reported (Fig. 4).…”
Section: Experiments 1 Instrumental Training Number Of Responses Tomentioning
confidence: 94%
“…Instrumental training Evidence from the PIT literature shows behavioral [13][14][15]19 and neural [16][17][18][20][21][22] dissociations between outcomespecific and general transfer. While general transfer is more dependent on the motivational properties of the Pavlovian cue, outcome-specific transfer is more related to the sensory-specific properties of the cue 23 .…”
Section: Task Phase Contingencymentioning
confidence: 99%
See 1 more Smart Citation
“…General behavioral invigoration of classically conditioned cues appears more difficult to demonstrate in humans. Among appetitive PIT studies examining the differential effects of outcome-specific vs. general behavioral activation, we identified only six reporting general transfer effects (Prevost et al, 2012;Watson et al, 2014;Hebart and Gläscher, 2015;Quail et al, 2017b;Alarcón and Bonardi, 2019;Garofalo et al, 2019). A small number of other human PIT studies used designs with a single excitatory cue, and reported transfer effects (Talmi et al, 2008;Lovibond and Colagiuri, 2013;Colagiuri and Lovibond, 2015;Pool et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PIT effects in humans have been shown to be insensitive to outcome-devaluation [253] (although see satiety effects in PIT-related NAcc activation in animals [254]), but sensitive to extinction, although this was less effective for reducing PIT in a different context [255]. Moreover, reduced working memory capacity has been reported to attenuate outcome-specific but not general PIT [256].…”
Section: Behavioral Paradigms and Neural Circuitrymentioning
confidence: 99%